Efek Dendrite Arm Spacing terhadap Sifat Mekanis Paduan Perunggu Cu-20%Sn - Sugita, I Ketut Gede; Soekrisno, R.; Miasa, I Made; -, Suyitno (Jurnal Energi Dan Manufaktur; Vol 4, No.2 Oktober 2010, 2012)
The purpose of this work is to investigate the effect of dendrite arm spacing on mechanical properties bronze20%Sn alloys The commercial pure copper and tin were melted in crucible furnace at temperature 1000oC. The molten metalwas casted in permanent moulds which have variation temperature, i.e. 35oC, 200oC, 400oC. The history of coolingtemperature on castings was recorded using a computer aided data acquisition Lab view 8.2 system.The microstructure and mechanical properties of this alloy have been investigated. The results of this researchindicate that decreasing the mould temperature affected on increasing solidification rate that caused to reduce thesolidification time. On the other hand, the difference of solidification rate have effected on microstructure forms. Thedendrite arm spacing (DAS) decreases with increasing solidification rate. DAS affected on mechanical properties i.e.ultimate tensile strength and hardness as cast. The mechanical properties increase with decreasing DAS.
Keywords: Tin bronze, dendrite, dendrite arm spacing (DAS), and microstructure